A case study: biocompost processing using empty fruit bunches (EFB) at Sedenak estate / Nur Farahin Mohd Fauzi - Mohd Fauzi, Nur Farahin (Faculty of Plantation and Agrotechnology, 2016)
This case study is to know the processing of biocompost using empty fruit bunch (EFB). The case study was conducted at Sedenak Estate and the project of biocompost plant operated by Semai A1am Sdn Bhd located at Ku1ai, lohor. The process of biocompost is determine by knowing the time and motion study of the process of biocompost using the EFB. From that process, the data that had been collected are the production of biocompost on productivity per hour and the total cost of biocompost processing using EFB. The result on production of biocompost productivity per hour are 109.44 mt. For the total cost operation are RM 742.67 per hour. This processing biocompost are suitable touse to the plantations and the farmers that can get the higher production with reasonable cost for that company.